REVIEW OF NORM DISTRIBUTION AND BEHAVIORS IN PRODUCED WATER FROM OILFIELD INDUSTRIES - Nacer , Hamza (SSD Journal, 2022)
According to the noteworthy concentration of naturally occurring radioactive material (NORM), produced water that is considered a damaging waste resulting from the oil extraction process according to the noteworthy concentration of naturally occurring radioactive material (NORM), is regularly disposed into nearby areas, resulting in environmental contamination that raises the possibility of human exposure NORM in various pathways. This paper purposes to provide an extensive examination of the NORM reported in produced water linked with oilfield activities from previous reports. The comparison of NORM values in oilfields around the world demonstrates a vivid understanding of radionuclide behaviors associated with oil extraction operations. The results illustrate that Radium isotopes are the most radionuclides abundant in produced water, especially Radium-226, activity concentrations of U-238 and Th-232 were remarkable to be low in the water. Oil extraction is increasing, leading to more produced water being disposed of, which is a real concern for human health, so a depth study is recommended to focus on minimization and other management methods of produced water instead of being disposed of. Furthermore, the NORM waste and its influence could be minimized by obeying the recommended standard set by IAEA and other environmental protection agencies.